Exacerbation of Subthreshold PTSD Symptoms in a Great East Japan Earthquake Survivor in the Context of the COVID-19 Pandemic - Arinobu Hori; Toyoaki Sawano; Akihiko Ozaki; Masaharu Tsubokura (Case Reports in Psychiatry)
Background. In 2011, the people of Fukushima, Japan, experienced the Great East Japan Earthquake (GEJE), a complex disaster of earthquake, tsunami, and nuclear accident. Its residents are experiencing a second global disaster, a COVID-19 pandemic in 2020. Objective. In this article, we aimed at discussing the effects of subthreshold PTSD in a previous disaster on an exacerbation of PTSD symptoms in another disaster. Method. We present a case of subthreshold PTSD in the context of a nuclear accident and exacerbation of symptoms due to the COVID-19 pandemic. Results. Exacerbation of subthreshold PTSD symptoms was likely due to the reemergence of an urgent atmosphere similar to the previously experienced traumatic event. Conclusions. PTSD may occur not only in those who experience the actual life-threatening like ICU admission but in those who experience the atmospheric change of society. This case demonstrated the characteristics of subthreshold PTSD caused by two disasters that shared a similar sense of insecurity, the scale of impact on the society, invisibility of the threat, restricted movement, and authoritative conflicts. These commonalities led to a recurrence and exacerbation of initial symptoms. This finding should be shared with those involved in the care system for victims’ mental health suffering from a large-scale disaster, and we need further research about the issue.